Chlorophyll-based photocatalysts and their evaluations for methyl orange photoreduction - Joshi, Meenal M.; Kamble, Sanjay R.; Labhsetwar, Nitin K.; Parwate, D. V.; Rayalu, Sadhana S. (Journal of Photochemistry and Photobiology A-Chemistry, 2009)
Immobilization of chlorophyll on different functionalized mesoporous materials has been attempted. The replacement of butanediol with monoethanol amine has resulted in increase in chlorophyll loading by a factor of two. The maximum immobilization of chlorophyll was on MCM-41 functionalized with monoethanolamine MCM-41/MEA/Chl) as compared to other mesoporous materials. This material has been characterized using XRD, UV-vis diffuse reflectance spectroscopy, scanning electron microscopy (SEM-EDX) and fluorescence spectroscopy. The photocatalytic reduction of methyl orange (MO)was studied using MCM-41/MEA/Chl as photocatalyst under the visible light. The photocatalytic reduction of MO was 0.396 mg/g of MCM-41/MEA/Chl photocatalyst as compared to 0.508 mg/g of TiO(2) for that of Degussa P-25 photocatalyst. The effect of various operating parameters like catalyst loading, initial concentration and intensity of light has also been studied. Photocatalytic property of chlorophyll-based photocatalytic material indicates that chlorophyll acts as a reaction center, which absorbs visible light and generates electron, which is transferred to different electron acceptors reducing MO into derivative of hydrazine. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Chlorophyll-based photocatalyst; Mesoporous material; Methyl orange; Photoreduction